Hiding in Plain Sight: Reproducing Masculine Culture at a Video Game Studio. (8th October 2013) - Johnson, Robin
Abstract: The growing body of research on the production of video games has underscored the disproportionate number of women to men working on the development and creation of digital games. What is not well documented is the role the cultural environment of video game studios plays in maintaining androcentrism. This article explains how discourses of masculinity influence work at a video game studio and how they reproduce a culture unwelcoming to most women. Using ethnographic methods and in-depth interviews, this analysis of a video game studio looks at the interplay of different types of masculinity and the role they play in the reproduction of masculine culture.